Perbandingan Efektivitas Sanksi Administratif Dan Pidana Terhadap Pelaku Kartel Di Indonesia - Dapurahayu, Sella; Jauharah, Sri Adisty; Pratama, Dendy Suma; Fitriani, Annisa; Siswajanthy,SH.,MH., Farahdinny (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Abstract This study compares the effectiveness of administrative and criminal sanctions against cartel offenders in Indonesia. The research method uses comparative analysis with secondary data from KPPU, the Ministry of Trade and the Criminal Justice Agency. The results show that criminal sanctions are more effective in preventing cartel actors, while administrative sanctions are more effective in improving compliance. This study recommends the integration of administrative and criminal sanctions, as well as increased inter-agency cooperation to improve the effectiveness of supervision and prosecution of cartel actors. Keywords: administrative sanctions, criminal sanctions, cartel cases, effectiveness Abstrak Penelitian ini membandingkan efektivitas sanksi administratif dan pidana terhadap pelaku kartel di Indonesia. Metode penelitian menggunakan analisis komparatif dengan data sekunder dari KPPU, Kementerian Perdagangan RI dan Badan Peradilan Pidana. Hasil penelitian menunjukkan bahwa sanksi pidana lebih efektif dalam mencegah pelaku kartel, sedangkan sanksi administratif lebih efektif dalam meningkatkan kepatuhan. Penelitian ini merekomendasikan integrasi sanksi administratif dan pidana, serta peningkatan kerjasama antarlembaga untuk meningkatkan efektivitas pengawasan dan penindakan terhadap pelaku kartel. Kata kunci : sanksi administratif, sanksi pidana, kasus kartel, efektivitas